Integrating gamification and GenAI to enhance EFL learning among higher education students - Kartika S (JEIT (Journal of Educational Innovations and Technologies), 2026)
The integration of digital technologies has become increasingly important in English as a Foreign Language (EFL) instruction in higher education, particularly for improving student engagement and learning outcomes. Among emerging innovations, gamification and GenAI(GenAI) have attracted growing attention for their potential to make language learning more interactive, motivating, and supportive. However, previous studies have more often examined these two approaches separately, leaving limited evidence on how their integration may influence EFL learning achievement and student perception, especially in non-English-major contexts in Indonesian higher education. This study therefore aimed to investigate the extent to which the integration of gamification and GenAI enhanced EFL learning achievement and how students perceived its use in English learning. This study employed an explanatory sequential mixed-methods design. The quantitative phase used a quasi-experimental pretest-posttest nonequivalent control-group design involving students of the Faculty of Shariah at UIN Raden Intan Lampung. Data were collected through pretest and posttest scores from experimental and control groups, followed by semi-structured interviews with selected students from the experimental group. The quantitative data were analyzed using descriptive statistics, paired-samples t-tests, independent-samples t-tests, and ANCOVA, while the qualitative data were analyzed through thematic analysis. The findings showed that the experimental group outperformed the control group in EFL learning achievement. The students also perceived the integration positively, particularly in terms of increased engagement, enjoyable learning experiences, and immediate linguistic support. These findings imply that integrating gamification and GenAI can serve as a promising instructional strategy for EFL learning in higher education, especially for non-English-major students.